As representações de natureza e o discurso do Movimento dos Atingidos por Barragens: uma leitura à partir do campo ambiental - Pinheiro, Claudiomiro Visca (2009)
The main proposal of this work is to make the analysis of the discourse of the Movement of Dam-Affected People (MAB). Search through the study of the nature of the representations contained in this speech, discussing some aspects that circumvent what today is called the environmental issue. In this case it is accepted the social constructionism and the use of methodological tools for the social field as argued in favor of the existence of several discursive matrices, which give the speech about the nature of the characteristic polyphony. Thus, the literature review and analysis of discourse seeks to discover historical and social training of the speech, and thus consider that these are constitutive and instrumental in its understanding. Begins with a brief contextualization of the concepts about the nature in the Western world throughout history, reaching the examination of the main currents of contemporary environmentalism. The chronicle reveals competition highlights the current discourse, in which the discourse has a membership required to depictions of nature through the ages. It is concluded that the speech of the Movement of Dam- Affected People has the structure necessary for the mobilization of affected communities, since it is used to anchor in the representations in the everyday life of these populations. Similarly the signs of a mythical character in the discourse of the movement are mobilizing society in general, given the strong presence of nature sanction in the popular imagination. From the perspective of constructionism, the environmental field and the discourse analysis, the position of actors and power relations in capitalist society, should be the main objects to be targeted if the goal is to understand what really is the nature in a discourse rather than what we pretend to common sense.